Shear Wave Elastography on the Uterine Cervix: Technical Development for the Transvaginal Approach - O'Hara, S.; Zelesco, M.; Sun, Zhonghua (American Institute for Ultrasound in Medicine, 2018)
Objectives: This research aimed to identify biological and technical confounders in the nonpregnant cervix when applying shear wave elastography with an endovaginal transducer. Methods: Cervical speed measurements were obtained at the internal and external os in the anterior and posterior portions of the cervix using a transvaginal approach in 69 nongravid patients. Results: Reliable measurements were obtained at the external os and internal os, anteriorly and posteriorly, in 63, 55, 55, and 26 patients, respectively. The mean speed obtained at the external os, anteriorly and posteriorly, was 2.52 ± 0.49 m/s and 2.87 ± 0.63 m/s, respectively, and at the internal os, anteriorly and posteriorly, 3.29 ± 0.79 m/s and 4.10 ± 1.11 m/s, respectively. The difference in speed between all regions was statistically significant (P < .05). Conclusion: Ultrasound‐induced artifacts appear to affect the transmission of the elastographic main pulse, with cervical position contributing to suboptimal shear wave production in the posterior cervix. Reliable shear wave propagation can be achieved in the anterior cervix in most patients.